Mitochondrially targeted p53 or DBD subdomain is superior to wild type p53 in ovarian cancer cells even with strong dominant negative mutant p53 - Phong Lu; Erica R. Vander Mause; Katherine E. Redd Bowman; Sarah M. Brown; Lisa Ahne; Carol S. Lim (BMC, 2019)
Abstract Background While tumor suppressor p53 functions primarily as a transcription factor in the nucleus, cellular stress can cause p53 to translocate to the mitochondria and directly trigger a rapid apoptotic response. We have previously shown that fusing p53 (or its DNA binding domain, DBD, alone) to the mitochondrial targeting signal (MTS) from Bak or Bax can target p53 to the mitochondria and induce apoptosis in gynecological cancer cell lines including cervical cancer cells (HeLa; wt p53), ovarian cancer cells (SKOV-3; p53 267del non-expressing), and breast cancer cells (T47D; L194F p53 mutation). However, p53 with Bak or Bax MTSs have not been previously tested in cancers with strong dominant negative (DN) mutant p53 which are capable of inactivating wt p53 by homo-oligomerization. Since p53-Bak or Bax MTS constructs act as monomers, they are not subject to DN inhibition. For this study, the utility of p53-Bak or p53-Bax MTS constructs was tested for ovarian cancers which are known to have varying p53 statuses, including a strong DN contact mutant p53 (Ovcar-3 cells), a p53 DN structural mutant (Kuramochi cells), and a p53 wild type, low expressing cells (ID8). Results Our mitochondrial p53 constructs were tested for their ability to localize to the mitochondria in both mutant non-expressing p53 (Skov-3) and p53 structural mutant (Kuramochi) cell lines using fluorescence microscopy and a nuclear transcriptional activity assay. The apoptotic activity of these mitochondrial constructs was determined using a mitochondrial outer membrane depolarization assay (TMRE), caspase assay, and a late stage cell death assay (7-AAD). We also tested the possibility of using our constructs with paclitaxel, the current standard of care in ovarian cancer treatment. Our data indicates that our mitochondrial p53 constructs are able to effectively localize to the mitochondria in cancer cells with structural mutant p53 and induce apoptosis in many ovarian cancer cell lines with different p53 statuses. These constructs can also be used in combination with paclitaxel for an increased apoptotic effect. Conclusions The results suggest that targeting p53 to mitochondria can be a new strategy for ovarian cancer treatment.